Introduction to law - Barte, Recaredo P. (Quezon City, Philippines : Central Book Supply, 2021)
Law-- in its generic sense, is a body of rules of action or conduct prescribed by controlling authority, and having binding legal force.
Chapter 1. Preliminary Considerations -- Chapter 2. Kinds of Laws -- Chapter 3. Law of persons and family relations-- Chapter 4. Sources and application of law -- Chapter 5. Origin and Application of laws -- Chapter 6. Persons and Family relations -- Chapter 7. Family relations and marriage -- Chapter 8. Legal Separation -- Chapter 9. Law on property -- Chapter 10. Special contracts -- Chapter 11. Remedial Law -- Chapter 12. Special civic actions.
Keywords: CIVIL LAW -- PHILIPPINES